Study of Development Trends and Development of Measures to Overcome Depopulation of Strategically Important Regions of Kazakhstan - K. I. Ibragimova; A. B. Turysbekova (Экономика: стратегия и практика, 2022)
This article deals with one of the most pressing issues today: the study of trends in the development and disappearance of the regions of Kazakhstan. The article discusses the features and opportunities of strategic development of regions in the Republic of Kazakhstan, as well as regional development trends and issues of regional extinction. The main relevance of the article is that it provides accurate information about trends in the development and disappearance of the regions of Kazakhstan. The purpose of the article is to consider possible ways to overcome negative trends in the country and improve depopulation and demographics. Scientific significance, Regional Development, and extinction issues, as well as comparative information on depopulation in the country, are presented. The practical significance of the work lies in the fact that the results of this work when studying demographics, become valuable information for students of higher educational institutions. The following research methods were used in the work: text analysis in the form of analysis of scientific literature affecting the study of demographics, comparative analysis in the form of study and generalization of information obtained during the study; as well as statistical methods, synthesis were used. As auxiliary methods of empirical research: comparison, generalization is used. The main conclusions and value of the study: the article presents the emergence of the problem of depopulation and the main reasons for the disappearance and depopulation of the regions of Kazakhstan. At the same time, the current state of development trends in Kazakhstan and current and new data on extinction and depopulation are provided.